Anuran development: A reinvestigation of the conus arteriosus and gill formation in Bufo bufo throughout metamorphosis using micro‐CT. Issue 5 (27th September 2021) - Kraus, Nina; Metscher, Brian
Abstract: Using high‐resolution X‐ray micro‐CT imaging of whole Bufo bufo specimens, we acquired detailed 3D descriptions of the changing morphology of the cardiac outflow structures, in particular the conus arteriosus through larval development and the transition. Previous findings regarding anuran conal structures were contradictory, depending on the specifics of the 2D imaging methods used by different authors. Our descriptions of conal morphology at different developmental stages show that early tadpoles initially only have one opening at the ventricular‐conal junction and only one cavum within their conus; however, the forming septum coni soon divides the conus into two chambers, the cavum pulmocutaneum and the cavum aorticum. This is accompanied by the development of a second small opening at the ventricular‐conal junction. The separated chambers continue into the aortic arches. Following the aortic arches into the area where gills will form, we describe how blood vessels associated with the external gills develop from vessels arising from the truncus arteriosus. The external gills soon undergo partial absorption. During the transition from external to internal gills, the gill filaments retreat asymmetrically into a gill chamber formed by a hyoidal cover contacting the animal's ventral side, leaving only a single opening on the animal's left side, the opercular spout. B. bufo retains its internal gills up to metamorphic climax, with the aortic arches arising from the conus arteriosus still leading into the gills. Our 3D image data are publicly available and will provide a sound morphological basis for future studies.